2022
DOI: 10.1038/s41598-022-08726-8
|View full text |Cite
|
Sign up to set email alerts
|

The beneficial effects of intradialytic parenteral nutrition in hemodialysis patients with protein energy wasting: a prospective randomized controlled trial

Abstract: In hemodialysis (HD) patients, protein-energy wasting (PEW) is highly prevalent and firstly treated with oral nutritional supplements (ONS). The extent to which intradialytic parenteral nutrition (IDPN) contributes to improve PEW status in HD patients intolerable to ONS remains unclear. Maintenance PEW HD patients being unable to tolerate ONS adverse effects, and having spontaneous energy and protein intake of ≥ 20 kcal/kg/day and ≥ 0.8 g/kg/day, respectively were randomly assigned 1:1 into IDPN and control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 44 publications
0
11
0
1
Order By: Relevance
“…In a recent randomized controlled trial between February 2020 and December 2020, 38 hemodialysis patients were divided into two groups as IDPN plus standard dietary counseling (IDPN group) and standard nutritional counseling (control group). The study showed that 3-month IDPN supplementation demonstrated a significant increase in serum albumin, body weight, spontaneous oral intake, and malnutrition inflammation score [52]. However, there are not enough studies yet to reach such a conclusion.…”
Section: Impact Of Other Nutritional Interventions On Muscle Wasting ...mentioning
confidence: 95%
“…In a recent randomized controlled trial between February 2020 and December 2020, 38 hemodialysis patients were divided into two groups as IDPN plus standard dietary counseling (IDPN group) and standard nutritional counseling (control group). The study showed that 3-month IDPN supplementation demonstrated a significant increase in serum albumin, body weight, spontaneous oral intake, and malnutrition inflammation score [52]. However, there are not enough studies yet to reach such a conclusion.…”
Section: Impact Of Other Nutritional Interventions On Muscle Wasting ...mentioning
confidence: 95%
“…Studies suggest that the combination of IDPN with oral nutritional supplements can improve markers of nutritional status, including dry body weight, skinfold measurements, and mid-arm muscle circumference, as well as serum albumin and prealbumin, in patients who cannot reach nutritional goals with oral supplements alone. 28,36,37 Earlier studies showed that IDPN can be safely used in the geriatric population. In a study including 78 elderly patients older than 70 years, IDPN was found to improve serum albumin and transferrin after 3 months and body anthropometric measurements after 6 months of treatment.…”
Section: Idpnmentioning
confidence: 99%
“…The mean age was 67.6610.8 years, and two patients with manageable hyperglycemia were observed in the IDPN group. 37 While IDPN is valuable in the management of patients who cannot tolerate adequate oral supplementation, it is unlikely to provide additional nutritional benefit when sufficient oral supplementation can be maintained. A randomized trial including 186 patients with a mean age of 68.869.9 years showed that adding IDPN to a regimen of oral supplementation that contained 500 kcal/d and 25 g/d protein did not offer nutritional or survival benefits in a follow-up period of 2 years.…”
Section: Idpnmentioning
confidence: 99%
“…According to the guidelines of the European Society for Clinical Nutrition and Metabolism (ESPEN), the first week should be started at no more than 8 mL/kg/IDPN (500 mL at 60 kg) and up to 16 mL/kg/IDPN at the maximum, and then, the dosage per dialysis should not exceed 1000 mL [ 82 ]. In a recent RCT on patients with HD, IDPN was administered to a group of patients who had adequate dietary intake (energy ≥ 20 kcal/kg/day, protein ≥ 0.8 g/kg/day) but were unable to continue ONS due to digestive symptoms [ 83 ], while the control group only received weekly nutritional counseling. At three months, serum albumin increased from 3.6 to 3.8 g/dL, and energy intake and body weight increased in the IDPN group (total energy: 1100 kcal, water: 986 mL, continuous administration over 4 h on dialysis) compared to the control group.…”
Section: Nutritional Supplementation For Pewmentioning
confidence: 99%